2020
DOI: 10.3390/ijerph17207562
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ecological Water Supplement Scheme for Improved Suitable Habitat Area for Rare Migratory Birds in Nature Reserves Using Interval-Parameter Fuzzy Two-Stage Stochastic Programming Model

Abstract: The optimization of ecological water supplement scheme in Momoge National Nature Reserve (MNNR), using an interval-parameter two-stage stochastic programming model (IPTSP), still experiences problems with fuzzy uncertainties and the wide scope of the obtained optimization schemes. These two limitations pose a high risk of system failure causing high decision risk for decision-makers and render it difficult to further undertake optimization schemes respectively. Therefore, an interval-parameter fuzzy two-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In order to solve the Yinma River Basin's water resource allocation model based on the IFTSP method, the objective functions f + and f − [63] of the IFTSP model were obtained first and then substituted into the IFTSP model as constraint conditions. Based on the interactive algorithm, the IFTSP model can be transformed into two groups of deterministic submodels [67,68] to solve the upper and lower bounds of the objective function, respectively. Lingo 11 software was used in this study to solve the developed IFTSP model, and the fuzzy membership degree interval was obtained as [0.32, 0.99].…”
Section: Resultsmentioning
confidence: 99%
“…In order to solve the Yinma River Basin's water resource allocation model based on the IFTSP method, the objective functions f + and f − [63] of the IFTSP model were obtained first and then substituted into the IFTSP model as constraint conditions. Based on the interactive algorithm, the IFTSP model can be transformed into two groups of deterministic submodels [67,68] to solve the upper and lower bounds of the objective function, respectively. Lingo 11 software was used in this study to solve the developed IFTSP model, and the fuzzy membership degree interval was obtained as [0.32, 0.99].…”
Section: Resultsmentioning
confidence: 99%
“…The model constructed in this paper focuses on economic development. Liao et al (22] focused on restoring the suitable habitat area of rare birds. This paper provides another scheme for decision-makers from the perspective of economic development, which is beneficial for decision-makers to comprehensively consider the actual situation of wetland water supply.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon sink capacity of ecological functional areas [ 22 ]: where denotes the NSC of the ecological function area for different regions after optimization (t); denotes the NSC capacity of the ecological function area of the lake (t/10 3 hm 2 ); and denotes the NSC in the ecological function area for different regions (t).…”
Section: Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has the advantage of not requiring the collection of a large amount of data for theoretical support [ 23 , 24 , 25 ]. Liao et al [ 26 ] optimized the ecological water refill scheme in the Momoge National Nature Reserve based on the interval-parameter two-stage stochastic programming model (IPTSP) and found that the fuzzy uncertainty that existed in the optimization process could lead to greater decision-making risks. Thus, they introduced the fuzzy optimization method for further optimization.…”
Section: Introductionmentioning
confidence: 99%